Wheat Cost-Return Budget in Southeast Kansas - Dumler, Troy J.; Shoup, Douglas (My University, 2008)
This publication outlines the expected costs and returns for wheat in southeast Kansas.
MF992_2008_10
Keywords: MF992; Economics; Crops; MF